The roles of extracellular vesicles in major depressive disorder - Li, Ying; Gui, Yan; Zhao, Miaomiao; Chen, Xuanqiang; Li, Haimei; Tian, Chen; Zhao, Haoyang; Jiang, Chaonan; Xu, Pengfeng; Zhang, Shiyi; Ye, Shaoyong; Huang, Manli (Frontiers in Psychiatry, 2023)
Major depressive disorder (MDD) is a serious mental disease characterized by depressed mood, loss of interest and suicidal ideation. Its rising prevalence has rendered MDD one of the largest contributors to the global disease burden. However, its pathophysiological mechanism is still unclear, and reliable biomarkers are lacking. Extracellular vesicles (EVs) are widely considered important mediators of intercellular communication, playing an important role in many physiological and pathological processes. Most preclinical studies focus on the related proteins and microRNAs in EVs, which can regulate energy metabolism, neurogenesis, neuro-inflammation and other pathophysiological processes in the development of MDD. The purpose of this review is to describe the current research progress of EVs in MDD and highlight their potential roles as biomarkers, therapeutic indicators and drug delivery carriers for the treatment of MDD.